2021
DOI: 10.1111/jce.15082
|View full text |Cite
|
Sign up to set email alerts
|

Atrial thrombus detection on transoesophageal echocardiography in patients with atrial fibrillation undergoing cardioversion or catheter ablation: A pooled analysis of rates and predictors

Abstract: Objective: To summarize data on the rates and predictors of left atrial thrombus/ left atrial appendage thrombus (LAT/LAAT) detection by transoesophageal echocardiography (TEE) before electrical cardioversion (ECV) or catheter ablation (CA) for atrial fibrillation (AF).Methods: EMBASE, MEDLINE, and Web of Science Core Collection were searched to identify all studies providing relevant data and published by October 7, 2020.A random-effects meta-analysis method was used to pool effect size estimates.Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
4
18
0
Order By: Relevance
“…Similar to our study, in a recent meta-analysis of observational studies, the prevalence of LA thrombus in 9772 anticoagulated patients undergoing TEE before cardioversion or catheter ablation was 6.7%, with higher prevalence in patients on VKA (12% on VKA vs. 4.7% on NOAC) [ 8 ]. In meta-analyses of randomized controlled trials compared to VKA, NOACs were shown to reduce all-cause mortality, as well as the risk of stroke or systemic embolism; the latter driven mainly by a ~50% reduction in hemorrhagic stroke [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our study, in a recent meta-analysis of observational studies, the prevalence of LA thrombus in 9772 anticoagulated patients undergoing TEE before cardioversion or catheter ablation was 6.7%, with higher prevalence in patients on VKA (12% on VKA vs. 4.7% on NOAC) [ 8 ]. In meta-analyses of randomized controlled trials compared to VKA, NOACs were shown to reduce all-cause mortality, as well as the risk of stroke or systemic embolism; the latter driven mainly by a ~50% reduction in hemorrhagic stroke [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…In terms of prevention of ischemic stroke, NOACs have demonstrated similar efficacy to VKA, with only a trend towards benefit with NOACs [ 10 ]. Lower relative efficacy of VKA in observational studies reporting on the prevalence of LA thrombus on TEE [ 8 , 11 ] could be explained by lower time in therapeutic range (TTR) in real-world patients [ 12 ] compared to TTR achieved in patients enrolled in clinical trials [ 13 ], and could imply even more benefit with NOACs compared to VKA in real-world AF population. Still, not every LA thrombus results in ischemic stroke and, thus, the higher prevalence of LA thrombus under VKA treatment might not necessarily translate into a higher risk of thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…Schaefer et al [28] had a higher incidence of LAAT (9.6%), which may be related to the lack of anticoagulation. Te prevalence rate of sludge and SEC was 1.0% and 9.7% in patients undergoing catheter ablation according to the recent meta-analysis [27], and basically the same rate as ours. AF type, LAD, age, BNP, and E/e' ratio were independent risk factors for predicting LA or LAA thrombi in this study.…”
Section: Discussionsupporting
confidence: 86%
“…However, almost all patients included in our center were first-diagnosed AF patients, and the proportion of oral anticoagulants was deficient. Based on a recent meta-analysis of left atrial appendage thrombi [ 27 ], we screened out studies that did not give oral anticoagulants before TEE. The incidence of LAAT in the selected studies ranged from 0% to 9.6% ( Table S1 ), which is basically in line with our incidence of LAAT.…”
Section: Discussionmentioning
confidence: 99%
“…If early CV is desirable, current guidelines recommend transesophageal echocardiography to exclude intracardiac thrombi [ 2 ]. In a recent meta-analysis, the pooled prevalence of left atrial thrombus in patients who were not on oral anticoagulation but were undergoing CV or catheter ablation was 1.8%; and the prevalence was significantly higher among patients with non-paroxysmal AF [ 34 ]. The main shortcoming of transesophageal echocardiography is that it only detects the pre-existing thrombi in the left atrium or left atrial appendage, and it cannot protect from thromboembolic complications caused by thrombi that are formed later, during the stunning phase after CV.…”
Section: How To Minimize the Risk Of Thromboembolic Complications Aft...mentioning
confidence: 99%